Factors That Influence the Selected Grade 12 Humanities and Social Sciences Students in Bestlink College of the Philippines in Utilizing Online Platforms: Basis for an Emerging Guide: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
AbstractThe popular online shopping platforms have attracted a lot of attention in recent years. Theresearchers have emphasized how crucial online platforms are to marketing since they candirectly affect customers' purchasing decisions because they can be perceived by consumersprior to consumption. This idea has been expanded in a variety of ways, from the physical tothe virtual marketplace, with the growth of online shopping. When consumers access almostall shopping platforms, the idea of "service" expands from its conventional meaning andincreasingly includes other novel conceptual elements. However, as online purchasing grows,it becomes more challenging to determine what high standards should apply to onlineshopping platforMs. to thoroughly investigate the potential applications of online shoppingplatforms in order to support effective purchasing behavior.after finishing the study, it is stated that the marketing strategy of sellers is the first reason whystudents recognize to use online platforms to purchase an item, and price is a hugecontribution to students preference in buying product as they prefer a product that is moreaffordable and more achieving for their budget, and product quality is one of the reason whystudents tend to buy more on online shopping and use online platforms and also one of thereason why the students stop purchasing is when they experience poor product quality.Knowing what to consider first before using online platforms to buy a product is effective for abetter shopping experience and achieving satisfaction in the shopping experience of buyers.Knowing what first to consider when using an online platform to purchase will make the persona wise consumer.
Keywords: Education